2019
DOI: 10.1103/physrevd.99.096018
|View full text |Cite
|
Sign up to set email alerts
|

Single and double nonlinear Compton scattering

Abstract: We study single, double and higher-order nonlinear Compton scattering where an electron interacts nonlinearly with a high-intensity laser and emits one, two or more photons. We study, in particular, how double Compton scattering is separated into one-step and two-step parts, where the latter is obtained from an incoherent product of two single-photon emissions. We include all contributions to double Compton scattering and show that the exchange term, which was not calculated in previous constant-crossed field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 87 publications
(212 reference statements)
3
83
0
Order By: Relevance
“…For a field with longer pulse length we have explicitly demonstrated that, unless b 0 is large or a 0 small, the one-step terms become negligible and so the two-step can indeed be used to approximate the probability. This is evidence in support of using our new gluing approximation [27,46] for studying other higher-order processes in long laser pulses with moderately high intensity a 0 1.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…For a field with longer pulse length we have explicitly demonstrated that, unless b 0 is large or a 0 small, the one-step terms become negligible and so the two-step can indeed be used to approximate the probability. This is evidence in support of using our new gluing approximation [27,46] for studying other higher-order processes in long laser pulses with moderately high intensity a 0 1.…”
Section: Discussionsupporting
confidence: 71%
“…A negligible twostep term will also occur if b 0 is not large, but a 0 is small. However, in that case we have no reason to neglect P 22 ex , which can be comparable to the other terms, as seen in The P 22→1 dir dominance is also interesting from a conceptual point of view, because, together with the twostep P 22→2 dir it can be obtained from our gluing approach [27,46]. The only difference consists in what step-function combination is put in the lightfront time integrand, see (B6).…”
Section: Numerical Study Of the Trident Spectramentioning
confidence: 99%
See 3 more Smart Citations